RARE CAUSES OF SPONTANEOUS PNEUMOTHORAX: TWO CASE REPORTS - V. Hadzhiminev (Trakia Journal of Sciences)
Secondary spontaneous pneumothorax (SSP) may be a result of different rare diseases. In the following article are presented two interesting cases of SSP related to genetic disorders – Ehlers-Danlos syndrome (EDS) and Neurofibromatosis type 1 (NF-1). We share our clinical, laboratory and imaging findings as well as the surgical techniques we used and the postoperative complications we had. We performed a detailed literature review on this topic.